THE ROLE OF CENTRAL BANKS IN POST-PANDEMIC ECONOMIC RECOVERY: REALITIES AND PERSPECTIVES - Marinela BĂRBULESCU; Alina HAGIU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
Romania's economy has honorably withstood the crisis caused by the covid-19 pandemic, given the limited budgetary space available to the authorities to intervene in support of companies and individuals affected by the virus and the restrictions imposed to limit its spread. The measures taken by the authorities to limit the effects of the pandemic have had mainly positive effects and the government's financing programs launched in this context have functioned largely due to the collaboration between the state and the banking system this time at the helm of the economy. Through this paper, we aim to highlight the support given by commercial banks to companies and individuals in order to recover the negative impact, through complex support policies that involved the mobilization and coordination of the authorities, especially the monetary and fiscal ones.